A novel indirect solar dryer with inlet fans powered by solar PV panels: Drying kinetics of Capsicum Annum and Abelmoschus esculentus with dryer performance. (December 2019) - Goud, Mallikarjuna; Reddy, Mugi Vishnu Vardhan; V.P., Chandramohan; S., Suresh
Highlights: An indirect type solar dryer with fans powered by solar PV panels was developed. Drying kinetics of green chilli and okra were estimated. Drying efficiencies were 9.15% (for green chilli) and 26.06% (for okra). The effective moisture diffusivities were calculated for green chilli and okra. Surface transfer coefficients and activation energy were estimated. Abstract: In the present work, an indirect type solar dryer (ITSD) was developed and its air flow was encouraged by inlet fans that operated by solar photovoltaic (PV) panels. Drying experiments were performed with green chilli (Capsicum Annum) and okra (Abelmoschus Esculentus). The drying kinetics and the performance parameters of ITSD were estimated. Green chilli and okra were reduced to final moisture content (MC) of 0.01001 and 0.12675 kg/kg of dry basis (db) from an initial MC of 8.3984 and 10.1234 kg/kg of db, respectively. The solar air collector efficiency and drying efficiency of 74.13, 9.15% and 78.30, 26.06%, respectively, were achieved during the drying of green chilli and okra. The average effective diffusion coefficient ( De ) was 1.8903 × 10 −9 m 2 /s and 6.0073 ×  10 −9 m 2 /s during drying of green chilli and okra, respectively. The average mass transfer coefficient ( hm ) and heat transfer coefficient ( h ) were 4.406 ×  10 −3 m/s, 5.075 W/m 2 K and 3.302 ×  10 −3 m/s, 3.804 W/m 2 K for green chilli and okra, respectively. The activation energy ( Ē ) for green chilli and okra was 24.135 and 21.523 kJ/mol, respectively. Significant improvement is noticed in the system when it is compared with the natural convection system. Uncertainty analysis was performed.